1990
DOI: 10.1088/0953-2048/3/11/006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quenching and lead substitution on the ultrasonic wave velocity and attenuation in bismuth cuprate high Tcsuperconductors

Abstract: The velocity and attenuation of longitudinal and shear ultrasonic waves propagated in ceramic specimens of single phase Bi(Pb)2223, Bi(Pb)2212 and lead-free Bi2212 have been measured between 10 and 295 K. The anomalous elastic effects and hysteresis in the range about 190-240 K reported by other workers have been found in samples of Bi(Pb)2223 and lead-free Bi2212. However, for the Bi(Pb)2212 phase, in which some Bi is substituted by Pb, these anomalies and hysteresis are suppressed. Quenching a sample of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The increase in absolute longitudinal and shear velocities at 80 K with x may be related to the decrease of cell volume as a result of substitution of smaller Sr 2+ (ionic radius: 1.25 Å) for Ba 2+ (ionic radius: 1.42 Å). This volume change may have caused changes in interatomic length and bonding strength which were detected by both longitudinal and shear phonons and are reflected by the increase in velocity for both modes with increasing Sr [21]. Interestingly, the substitution of Sr for Ba which caused a decrease in T c has also caused an increase in  D (Table 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase in absolute longitudinal and shear velocities at 80 K with x may be related to the decrease of cell volume as a result of substitution of smaller Sr 2+ (ionic radius: 1.25 Å) for Ba 2+ (ionic radius: 1.42 Å). This volume change may have caused changes in interatomic length and bonding strength which were detected by both longitudinal and shear phonons and are reflected by the increase in velocity for both modes with increasing Sr [21]. Interestingly, the substitution of Sr for Ba which caused a decrease in T c has also caused an increase in  D (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…The ultrasonic method, which is sensitive to lattice instabilities and phase transitions, was found to be very useful to probe bulk property changes of ceramic materials such as glasses [8][9][10][11], magnetoresistance materials [12][13][14][15], and also high-temperature superconductors [16-24 and references therein]. In the latter, step-like velocity anomalies above 200 K indicating sudden or unexpected elastic hardening taking place in superconducting samples have been observed in several RE123 [16,17], RE1113 [20] and Bi-based samples [18,21]. The step-like anomalies were found to be oxygen related but its relationship to superconductivity is still not clear [23].…”
Section: Introductionmentioning
confidence: 99%
“…Inhomogeneous temperature distributions introduce thermal stresses in the materials. Assuming that the the hot zone is spherical, the stresses induced at the interfaces of hot and cold zones can be calculated as [ 131 where (5, is the compressive stress in radial direction, oee and oqp9 are the tensile stresses on the surface of the sphere, a is radius of the sphere, r is the distance to the centre of the sphere, E (41 GPa [14]) is Young's modulus, ' U (assume 0.2) is Poisson's ratio and a is the thermal expansion coefficient [15]; q 8 and ovv are plotted in Fig. 11.…”
Section: Materials Thermo-mechanical Modellingmentioning
confidence: 99%
“…Amongst the normal state peculiarities being investigated are the pseudogap, superconducting fluctuation behavior (SFB) and elastic anomalies which occurs above the critical temperature T c . The elastic anomalies can be studied using velocity measurements and several reports have suggested that the anomalies correspond to lattice instabilities and phase transition around the critical temperature and between 180 K and 230 K [1][2][3][4][5][6][7]. Although the discovery of D-wave superconductivity in high-temperature superconductors concludes that the superconductivity mechanism of HTSC does not involve phonons, the continued observation of a number of elastic anomalies in the normal state remains intriguing as they may influence other material properties an act as precursor to physical changes at much lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For REBa 2 Cu 3 O 7 À δ (RE¼Y, Ho, Gd, Eu, Dy and Er) systems, a number of elastic anomalies have been reported in the temperature range of 200-260 K [3,4,6,[8][9][10][11][12][13] which were characterized by step-like slope change showing sudden hardening below certain temperature. Interestingly, previous work has also shown that the step-like elastic anomalies can also be influenced by elemental substitution.…”
Section: Introductionmentioning
confidence: 99%